Paradigma UMKM melalui QRIS: Dampak terhadap Keuangan, Konsumen, dan Kesiapan SDM - Mercidominick Fidelius Conrad Menachem Purba; Akhmad Oktiovani Rozikin; Ninik Fidiyah; Angel Novita Widjoyo; Selvi Nur Annisa (BIP's JURNAL BISNIS PERSPEKTIF, 2026)
Digital transformation in payment systems is a strategic factor in driving financial inclusion for MSMEs. The implementation of the Quick Response Code Indonesian Standard (QRIS) presents a non-cash payment innovation that improves transaction efficiency and market access. However, limited financial literacy and human resource (HR) readiness remain challenges. This study aims to analyze the impact of QRIS adoption on MSME financial performance, consumer behavior, and HR readiness within a single integrated analytical framework. The study used a quantitative approach with the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method through SmartPLS 4. The sample was determined by purposive sampling with reference to the 10-times rule, including MSME users or potential users of QRIS. Data were obtained through a 1–5 Likert scale questionnaire and supporting literature. The results showed that QRIS adoption significantly influenced MSME performance and consumer behavior. HR readiness had a positive effect on MSME performance, but not significantly on consumer behavior. The moderating role of HR readiness was also not proven. Prediction tests (PLSpredict and CVPAT) confirmed the model's strong predictive ability, particularly for MSME performance. This study contributes theoretically by developing an integrative conceptual model based on financial literacy, TAM, and organizational capabilities. Practically, the research findings can serve as a reference for regulators and digital financial service providers in designing more adaptive QRIS adoption strategies and MSME mentoring.